2022
DOI: 10.3390/ijms23105390
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Unsaturated Fatty Acid Docosahexaenoic Acid in the Central Nervous System: Molecular and Cellular Insights

Abstract: Fatty acids (FAs) are essential components of the central nervous system (CNS), where they exert multiple roles in health and disease. Among the FAs, docosahexaenoic acid (DHA) has been widely recognized as a key molecule for neuronal function and cell signaling. Despite its relevance, the molecular pathways underlying the beneficial effects of DHA on the cells of the CNS are still unclear. Here, we summarize and discuss the molecular mechanisms underlying the actions of DHA in neural cells with a special focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 195 publications
0
16
0
Order By: Relevance
“…It is suggested that these interventions should be considered as integral parts of MDD treatment, particularly in cases of its co-morbidity with substance use and alcohol dependence [ 169 ]. Another established therapy was proposed by clinical studies that revealed positive effects of the omega-3 fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), antioxidant and anti-inflammatory agents, in patients with depression and impulsivity [ 266 , 267 ]. Deprivation of dietary n-3 polyunsaturated fatty acid, a known antioxidant, has been found to increase both depression and aggressive behaviour in rats [ 268 ].…”
Section: New Strategies In Pharmacological Management Of Pathological...mentioning
confidence: 99%
“…It is suggested that these interventions should be considered as integral parts of MDD treatment, particularly in cases of its co-morbidity with substance use and alcohol dependence [ 169 ]. Another established therapy was proposed by clinical studies that revealed positive effects of the omega-3 fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), antioxidant and anti-inflammatory agents, in patients with depression and impulsivity [ 266 , 267 ]. Deprivation of dietary n-3 polyunsaturated fatty acid, a known antioxidant, has been found to increase both depression and aggressive behaviour in rats [ 268 ].…”
Section: New Strategies In Pharmacological Management Of Pathological...mentioning
confidence: 99%
“…Palmitic acid and stearic acid have been proven to increase amyloid protein in cortical neurons and promote tau hyperphosphorylation. DHA (Bazan et al, 2011;Petermann et al, 2022) and EPA (Shahidi, 2018) are unique polyunsaturated fatty acids, which can regulate synaptic function and improve salient transmission, and have great significance in neurodegenerative diseases. BAs eliminate liver cholesterol, a crucial factor in AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not known to what extent individual LC-PUFA concentrations reflect the content of these fatty acids in tissues, particularly in the brain. Studies in isolated cell systems have shown that precursors of DHA are transferred from plasma to astrocytes, where they are converted to DHA before they are taken up by neurons [7]. This pathway of DHA synthesis in the central nervous system appears to occur in vivo in some animal species, but it is not known to what extent this occurs in humans.…”
Section: Estimates Of the Need For Long Chain-polyunsaturated Fatty A...mentioning
confidence: 99%